2023
DOI: 10.3390/biomedicines11030826
|View full text |Cite
|
Sign up to set email alerts
|

The Role of ERα and ERβ in Castration-Resistant Prostate Cancer and Current Therapeutic Approaches

Abstract: Castration-resistant prostate cancer, or CRPC, is an aggressive stage of prostate cancer (PCa) in which PCa cells invade nearby or other parts of the body. When a patient with PCa goes through androgen deprivation therapy (ADT) and the cancer comes back or worsens, this is called CRPC. Instead of androgen-dependent signalling, recent studies show the involvement of the estrogen pathway through the regulation of estrogen receptor alpha (ERα) and estrogen receptor beta (ERβ) in CRPC development. Reduced levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 166 publications
(219 reference statements)
0
0
0
Order By: Relevance
“…In our study, the AMRs of ovarian cancer, leukemia, prostate, lip/oral/pharyngeal, pancreatic, and breast cancers increased significantly beyond the predicted rates, especially in 2022. All of these cancers are known as estrogen and estrogen receptor alpha (ERα)-sensitive cancers [78][79][80][81][82][83]. Recent research by Solis et al on the binding ability of S-protein of SARS-CoV-2 against over 9,000 human proteins has shown that S-protein specifically binds to ERα and upregulates the transcriptional activity of ERα.…”
Section: Cancer Development By Sars-cov-2 Mrna Vaccinementioning
confidence: 99%
“…In our study, the AMRs of ovarian cancer, leukemia, prostate, lip/oral/pharyngeal, pancreatic, and breast cancers increased significantly beyond the predicted rates, especially in 2022. All of these cancers are known as estrogen and estrogen receptor alpha (ERα)-sensitive cancers [78][79][80][81][82][83]. Recent research by Solis et al on the binding ability of S-protein of SARS-CoV-2 against over 9,000 human proteins has shown that S-protein specifically binds to ERα and upregulates the transcriptional activity of ERα.…”
Section: Cancer Development By Sars-cov-2 Mrna Vaccinementioning
confidence: 99%
“…For instance, the activation of ERα and ERβ promoted the migration, cell invasion and colony formation abilities in hormone-independent prostate cancer cells [ 10 ]. In addition, the development of prostate cancer into denuded resistant prostate cancer is mediated by ERα and ERβ [ 11 ]. So, targeting ER could be an option for discovery of novel compound for treating prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of the androgen receptor (AR) pathway in PCa development and progression, androgen deprivation therapy (ADT) has been perceived as the firstline therapeutic strategy against PCa [3]. Although these advances provided temporary respite, most patients inevitably develop a lethal form called metastatic castrationresistant prostate cancer (mCRPC), with a median survival of about 3 years [4], which remains a critical clinical challenge.…”
Section: Introductionmentioning
confidence: 99%